ACTH Level and Sodium-Potassium Ratio in Screening of Primary Canine Hypoadrenocorticism - Liliane Simpson-Louredo; Andrés Araújo Gutierrez; Ana Luíza Mattos-Guaraldi (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
This article describes a primary hypoadrenocorticism (HA) case report in a spayed mix-breeded German shepherd ten years old female dog that had unspecifi c symptoms during a week. The initial suspicious were poisoning and after, renal insuffi ciency, since laboratorial exams demonstrated azotemia.In both cases, the treatment were unsuccessfully. After laboratory exams and blood sodium: potassium ratio (Na: K) measure (23:1), the presumptive diagnosis was primary HA, that it was confi rmed by plasma adrenocorticotropic hormone (ACTH) level (280 pg/mL). Although the gold standard test to confirm HA is ACTH stimulation test, in many situations this exam is not feasible, once synthetic ACTH is expensive and often unavailable, especially in developing countries. In the case related here, only Na: K and plasma ACTH level were used as an alternative method to identify primary HA properly, associated to clinical signs,which was confi rmed by full recovery of the patient after indicated therapy.